Plasma phospholipid fatty acids are associated with altered fibrin clot properties in a population-based setting. (April 2019) - de Lange, Z.; Kahler, B.; Smuts, C.M.; Pieters, M.
Highlights: What is known on this topic? Blood levels of various fatty acids are emerging as modifiable biomarkers for chronic diseases such as CVD. Blood fatty acids can contribute to CVD via its effects on thrombus structure and composition. Specific effects of individual fatty acids on clot properties are, however, contradictory and inconsistent because of differences in study designs. What this paper adds? Plasma phospholipid fatty acids associated with both prothrombotic and profibrinolytic clot phenotypes in a population-based study - these associations were partly mediated by fibrinogen and BMI. Individual fatty acids from the same composite group often presented opposing associations with clot properties. Abstract: Evidence regarding the relationship of plasma clot properties with fatty acids is contradictory, owing to different experimental protocols employed. The relationship of fibrinogen and plasma fibrin clot properties with plasma phospholipid fatty acids were cross-sectionally investigated in a population-based setting in 900 individuals. Composite saturated fatty acids (driven by stearic acid) and composite n-3 and n-6 polyunsaturated fatty acids (driven by docosahexaenoic and arachidonic acid respectively) were associated with prothrombotic clot properties. Composite monounsaturated fatty acids (driven by oleic acid) were associated with a profibrinolytic clot phenotype. Fibrinogen and BMI partly mediated these relationships. Individual plasma fatty acids from the same composite group had opposing associations with clot properties indicating that associations with composite fatty acid groups is dependent on the relative composition of the comprising fatty acids. The relationship of the plasma phospholipid fatty acid profile with disease should not be interpreted without considering the role of regulatory mechanisms.